Role of Stakeholders in Millennial Smartfarming Program in Ciburial Village - Pratama, Yudhistira Anugerah; Nulhaqim, Soni Akhmad; Sulastri, Sri (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This research aims to obtain an overview and analysis of role of stakeholders in empowering millennial farmers through Millennial Smartfarming Program in Ciburial Village. This includes roles of government, local organizations and communities, academics, companies, and media. The study employs a qualitative approach involving 39 stakeholders as informants. For data collection, the researcher utilized observation, literature studies, documentation studies, and interviews. Results indicate that all stakeholders have actively contributed to success of Millennial Smartfarming Program in Ciburial Village. However, the involvement of media was not found, which is a concern for optimizing the program's success. Millennial Smartfarming Program in Ciburial Village also aligns closely with the conceptual framework used by the researcher. Nevertheless, there are still aspects of each stakeholder that need improvement. Therefore, parties such as head of Sukarame Village, head of Jamburaya Hamlet, all hamlets, and all neighborhoods in Ciburial Village, as well as millennial farmers, need to collaborate and build external relationships with outside parties, such as academics and companies, to sustain and enhance the success of Millennial Smartfarming Program in Ciburial Village. This collaboration will help millennial farmers achieve a better quality of life. The researcher also recommends involving the media to strengthen documentation and evaluation of the program and to build a broad network that supports the rights of millennial farmers and promotes positive social change in the community.